SUBSTANTIATION OF FACTORS INFLUENCING THE MODELING OF CONTAINER TRANSPORTATION IN RAILWAY TRANSPORT - Akhmatov Navruz Bakhtiyorovich (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
The main objective of the work is to study the justification of factors affecting the organization of container transportation in railway transport. In this article, an analysis of influencing factors, their description and impact was carried out, and on this basis, relevant information on the topic under consideration was identified. In addition, the article presents the possibilities of building a mathematical model by substantiating influencing factors. Influencing factors, economic growth, modern technologies, political stability, environmental demand, terminal structure, modeling.